Implementasi Metode Brainstorming dalam Pembelajaran Fikih Kelas X MA Mamba’ul Ulum Megaluh Jombang - Revin Fajariyatul Chuzairoh; Emi Lilawati; M. Aliyul Wafa (Lembaga Yasin AlSys, 2026)
Although the brainstorming method has been widely studied in learning contexts, research specifically discussing its application in Fikih learning for Grade X at MA Mamba’ul Ulum Megaluh Jombang remains limited. This study aims to analyze the application of the brainstorming method in improving students’ understanding in Fikih learning and to identify the supporting and inhibiting factors in its implementation. This study used a qualitative approach with a descriptive phenomenological design. The research informants included Fikih teachers and Grade X students selected through purposive sampling. Data were collected through observation, interviews, and documentation, and were then analyzed through the stages of data reduction, data display, conclusion drawing, and verification. The results showed that the application of the brainstorming method was able to create a more active, interactive, communicative, and participatory learning atmosphere. This method encouraged students to express ideas, engage in discussion, exchange opinions, and understand Fikih material more deeply. The supporting factors for its application included the teacher’s role as a facilitator, an open classroom atmosphere, and students’ courage in expressing opinions. Meanwhile, the inhibiting factors included differences in students’ characteristics and abilities, low self-confidence, lack of readiness for the material, and limited learning time. These findings contribute to the development of active learning based on social constructivism and expand understanding of the use of the brainstorming method in Fikih learning. This study concludes that the teacher’s role, student readiness, and effective time management are important factors in optimizing the application of the brainstorming method. The implication is that Fikih teachers need to combine this method with other learning strategies so that the learning process becomes more participatory, contextual, and meaningful.